Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1093/ije/dym275
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of visceral leishmaniasis in East Africa: a case-control study in Pokot territory of Kenya and Uganda

Abstract: Background In East Africa, visceral leishmaniasis (VL) is endemic in parts of Sudan, Ethiopia, Somalia, Kenya and Uganda. It is caused by Leishmania donovani and transmitted by the sandfly vector Phlebotomus martini. In the Pokot focus, reaching from western Kenya into eastern Uganda, formulation of a prevention strategy has been hindered by the lack of knowledge on VL risk factors as well as by lack of support from health sector donors. The present study was conducted to establish the necessary evidence-base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
5
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 32 publications
(29 reference statements)
9
90
5
8
Order By: Relevance
“…It was not possible to carry out a socioeconomic analysis due to lack of case information. Several studies in other areas have reported that socioeconomic variables, such as household structure, malnutrition and poverty are important risk factors for visceral leishmaniasis 33,34,35 and we therefore suggest that further research should be carried in this field.…”
Section: Cluster Analysismentioning
confidence: 82%
“…It was not possible to carry out a socioeconomic analysis due to lack of case information. Several studies in other areas have reported that socioeconomic variables, such as household structure, malnutrition and poverty are important risk factors for visceral leishmaniasis 33,34,35 and we therefore suggest that further research should be carried in this field.…”
Section: Cluster Analysismentioning
confidence: 82%
“…This has been reported previously. 19,20,[22][23][24][25] It is unclear whether this is because of factors such as increased exposure, vulnerability, or health-seeking behavior (it is possible that male patients are more likely to present to health centers for care) and how these factors vary in the different epidemiological and cultural settings. Populations were younger in Latin America than in Africa and South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of these parasite, human, and social components is central to developing and targeting interventions for VL. 20,39 Women of reproductive age (15-42 years of age) constitute variable proportions of the total VL patient populations (from 6.2% in Brazil to 26.3% in Nepal). This information is important for selecting an appropriate treatment and riskmonitoring strategy to protect this vulnerable and underresearched group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landscape variables such as land use/land cover (LULC) may be particularly important since they are directly linked to vector presence (Feliciangeli et al, 2006). The importance of LULC for sand fly distribution is emphasised by authors using vegetation and other environmental parameters, including meteorological and altitude data, to estimate the geographic limits for various vector species (Sudhakar et al, 2006;Kolaczinski et al, 2008;Bhunia et al, 2010b;Fernández et al, 2010). In this connection, the excellent spatial and spectral resolutions of currently available satellite sensors provide opportunities to explore transmission patterns, distances and environmental factors.…”
Section: Introductionmentioning
confidence: 99%